Geology and evolution of the Cortes de Pallás diapir (Eastern Iberia) - Óscar Navarro-Carrasco; Ignacio Meléndez-Hevia (Journal of Maps, 2020)
This paper presents an 1:20,000 geological map and cross-sections of the Cortes de Pallás diapir (eastern Iberia). This structure is located at the junction of the Iberian Chain and the Betic Cordillera, in the northernmost part of the eastern Prebetic Zone. The diapir is an ENE to NE oriented saltwall, parallel to the regional structural trend of the Betic Cordillera. Our results support the hypothesis of a polyphase tectonic evolution from Oligocene to Pliocene times: (a) An extensional phase, Oligocene–Early Miocene in age, in which the graben system formed and the diapir rose. (b) A Middle Miocene compressive phase characterized by at least the partial closure of the diapir and thrusting of its old southern margin over the previous half-graben infill. (c) Finally, a Late Miocene–Pliocene extensional phase in which, synchronous to the normal faulting in the graben system, the diapir was reactivated and cut the previous structures.